Msi2‐mediated MiR7a‐1 processing repression promotes myogenesis. Issue 1 (8th December 2021) - Yang, Wenjun; Yang, Lele; Wang, Jianhua; Zhang, Yuanyuan; Li, Sheng; Yin, Qi; Suo, Jinlong; Ma, Ruimiao; Ye, Yuzhen; Cheng, Hong; Li, Jinsong; Hui, Jingyi; et al.
Abstract: Background: Most of the microRNAs (MiRs) involved in myogenesis are transcriptional regulated. The role of MiR biogenesis in myogenesis has not been characterized yet. RNA‐binding protein Musashi 2 (Msi2) is considered to be one of the major drivers for oncogenesis and stem cell proliferation. The functions of Msi2 in myogenesis have not been explored yet. We sought to investigate Msi2‐regulated biogenesis of MiRs in myogenesis and muscle stem cell (MuSC) ageing. Methods: We detected the expression of Msi2 in MuSCs and differentiated myotubes by quantitative reverse transcription PCR (RT‐qPCR) and western blot. Msi2‐binding partner human antigen R (HuR) was identified by immunoprecipitation followed by mass spectrometry analysis. The cooperative binding of Msi2 and HuR on MiR7a‐1 was analysed by RNA immunoprecipitation and electrophoresis mobility shift assays. The inhibition of the processing of pri‐MiR7a‐1 mediated by Msi2 and HuR was shown by Msi2 and HuR knockdown. Immunofluorescent staining, RT‐qPCR and immunoblotting were used to characterize the function of MiR7a‐1 in myogenesis. Msi2 and HuR up‐regulate cryptochrome circadian regulator 2 (Cry2) via MiR7a‐1 was confirmed by the luciferase assay and western blot. The post‐transcriptional regulatory cascade was further confirmed by RNAi and overexpressing of Msi2 and HuR in MuSCs, and the in vivo function was characterized by histopathological and molecular biological methods in Msi2 knockout mice. Results: We identified a post‐transcription regulatory cascade governed by a pair of RNA‐binding proteins Msi2 and HuR. Msi2 is enriched in differentiated muscle cells and promotes MuSC differentiation despite its pro‐proliferation functions in other cell types. Msi2 works synergistically with another RNA‐binding protein HuR to repress the biogenesis of MiR7a‐1 in an Msi2 dose‐dependent manner to regulate the translation of the key component of the circadian core oscillator complex Cry2. Down‐regulation of Cry2 (0.6‐fold, vs. control, P  < 0.05) mediated by MiR7a‐1 represses MuSC differentiation. The disruption of this cascade leads to differentiation defects of MuSCs. In aged muscles, Msi2 (0.3‐fold, vs. control, P  < 0.01) expression declined, and the Cry2 protein level also decreases (0.5‐fold, vs. control, P  < 0.05), suggesting that the disruption of the Msi2‐mediated post‐transcriptional regulatory cascade could attribute to the declined ability of muscle regeneration in aged skeletal muscle. Conclusions: Our findings have identified a new post‐transcriptional cascade regulating myogenesis. The cascade is disrupted in skeletal muscle ageing, which leads to declined muscle regeneration ability.